Temper outbursts in Prader–Willi syndrome: causes, behavioural and emotional sequence and responses by carers. (4th February 2013) - Tunnicliffe, P.; Woodcock, K.; Bull, L.; Oliver, C.; Penhallow, J.
Abstract Background Temper outbursts are common in Prader–Willi syndrome but rarely described in detail. This study investigated the phenomenology of temper outbursts in terms of antecedents, sequence of behaviours and emotions and intervention strategies used. Method A semi‐structured interview about temper outbursts was conducted with the main carers of seven children (9.5 to 16.7 years) and seven adults (24.7 to 47.10 years) with Prader–Willi syndrome (10 male, 4 female). Reliability and validity of the interview results was established. Results Various setting events increased and reduced the likelihood of temper outbursts. The most common antecedent was a change to routine or expectation. There were marked similarities in the sequence of behaviours and emotions during temper outbursts, with anger rising quickly followed by expressions of remorse and distress at the end of an outburst. Discussion The sequence of behaviours and emotions within outbursts was similar to that described in temper tantrums in typical development. Cognitive and emotional processes are likely to be important in the understanding of temper outbursts with implications for early intervention.